Using the first law of thermdynamics prove derive cp-cv=r
Answers
Answered by
7
hey there !!
we know that :-
=) dH = dE + pdv ------(1)
we also know that
dH = (Cp)dt , dE = (Cv)dt
and pdv = Rdt
so put this in eqn 1
=) (Cp)dt = (Cv)dt + Rdt
=) cancel out "dt " from both the sides 'we get
=) Cp = Cv + R
=) Cp -Cv = R
--------________________________
Hope it helps
we know that :-
=) dH = dE + pdv ------(1)
we also know that
dH = (Cp)dt , dE = (Cv)dt
and pdv = Rdt
so put this in eqn 1
=) (Cp)dt = (Cv)dt + Rdt
=) cancel out "dt " from both the sides 'we get
=) Cp = Cv + R
=) Cp -Cv = R
--------________________________
Hope it helps
Answered by
1
hope it's help u......
Attachments:
![](https://hi-static.z-dn.net/files/d1a/ef71c4efd9cbaa6fe0a0371377029da5.jpg)
Similar questions